Primary anaplastic large cell lymphoma of the breast arising in reconstruction mammoplasty capsule of saline filled breast implant after radical mastectomy for breast cancer: an unusual case presentation - Sur Monalisa; Ross Cathy; Bishara Mona RY (BMC, 2009)
Abstract Background Primary non-Hodgkin lymphoma (NHL) of the breast represents 0.04-0.5% of malignant lesions of the breast and accounts for 1.7-2.2% of extra-nodal NHL. Most primary cases are of B-cell phenotype and only rare cases are of T-cell phenotype. Anaplastic large cell lymphoma (ALCL) is a rare T-cell lymphoma typically seen in children and young adults with the breast being one of the least common locations. There are a total of eleven cases of primary ALCL of the breast described in the literature. Eight of these cases occurred in proximity to breast implants, four in relation to silicone breast implant and three in relation to saline filled breast implant with three out of the eight implant related cases having previous history of breast cancer treated surgically. Adjuvant postoperative chemotherapy is given in only one case. Secondary hematological malignancies after breast cancer chemotherapy have been reported in literature. However in contrast to acute myeloid leukemia (AML), the association between lymphoma and administration of chemotherapy has never been clearly demonstrated. Case Presentation In this report we present a case of primary ALCL of the breast arising in reconstruction mamoplasty capsule of saline filled breast implant after radical mastectomy for infiltrating ductal carcinoma followed by postoperative chemotherapy twelve years ago. Conclusion Primary ALK negative ALCL arising at the site of saline filled breast implant is rare. It is still unclear whether chemotherapy and breast implantation increases risk of secondary hematological malignancies significantly. However, it is important to be aware of these complications and need for careful pathologic examination of tissue removed for implant related complications to make the correct diagnosis for further patient management and treatment. It is important to be aware of this entity at this site as it can be easily misdiagnosed on histologic grounds and to exclude sarcomatoid carcinoma, malignant melanoma and pleomorphic sarcoma by an appropriate panel of immunostains to arrive at the correct diagnosis of ALCL.